Implementing Basic Computer Terms in the Framework of Cognitive Lexicology - Lobar Usmanova Abduvasilovna (Researchparks Publishing, 2022)
With the development of cognitive terminology, the cognitive mechanism for nominating terms has become the focus of terminology research. Thus, the methods of forming computer terms in the developing informatics has become the most elevant research topic. This article is devoted to the semantic interpretation of basic computer terms within the framework of cognitive terminology based on a systematic approach to the phenomenon of metaphorization.